2018
DOI: 10.17584/rcch.2018v12i2.7652
|View full text |Cite
|
Sign up to set email alerts
|

Leaf area and intermittent misting on hop plants propagation by stem cuttings

Abstract: Hop (Humulus lupulus L.) is a plant with economic importance due to its use in the brewing industry. The cones produced by the species contain the main substances responsible for the beer’s bitterness and aroma. Hop plants cultivation in Brazil is still incipient and information on efficient methods for its propagation in this context are scarce. The objective of the present study was to evaluate the effect of different leaf areas (two whole leaves, two leaves in half, one whole leaf, one leaf in half and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…New studies on hop cuttings were found in the researched databases only in 2018. Gomes et al (2018) evaluated the rooting of cuttings of the cultivar Chinook, with different leaf areas in environments with and without intermittent mist. Cuttings with a pair of whole leaves, a pair of leaves with half the leaf area, a whole leaf, a leaf with half the leaf area, and without leaves were compared.…”
Section: Vegetative Propagation By Cuttingsmentioning
confidence: 99%
“…New studies on hop cuttings were found in the researched databases only in 2018. Gomes et al (2018) evaluated the rooting of cuttings of the cultivar Chinook, with different leaf areas in environments with and without intermittent mist. Cuttings with a pair of whole leaves, a pair of leaves with half the leaf area, a whole leaf, a leaf with half the leaf area, and without leaves were compared.…”
Section: Vegetative Propagation By Cuttingsmentioning
confidence: 99%
“…Although hop plants are clonally propagated for commercial purposes (GOMES et al, 2018;MACHADO et al, 2018), sexual propagation is a fundamental feature of breeding programs and, therefore, the determination of seed quality and standardization of germination tests are strategic approaches for the efficient production of new cultivars.…”
Section: Introductionmentioning
confidence: 99%